Clinical course of pregnancy and postpartum in a multidrug-resistant tuberculosis/HIV co-infected patient receiving bedaquiline-containing regimen as antimycobacterial therapy - О.М. Raznatovska; S.I. Tertishniy; V.G. Syusyuka; A.V. Fedorec; T.K. Sahaidak; T.A. Grekova; M. O. Shalmina; S.M. Makhonchuk (Infusion & Chemotherapy, 2019)
Background. According to World Health Organization (WHO), experimental studies performed in rats and rabbits have revealed no evidence of harmful side effects of bedaquiline to the fetus. WHO points out that, given the lack of adequate and controlled studies on the effects of bedaquiline on the fetus in pregnant women, and the fact that drug data regarding teratogenicity are limited to nonclinical animal data, this drug may be used when an effective treatment regimen cannot otherwise be provided. However, WHO recommends thorough registering treatment, pregnancy, and postpartum bedaquiline-related outcomes to provide data on appropriate dosing for multidrug-resistant tuberculosis (MDR-TB) treatment during pregnancy and postpartum. However, in the modern literature, there are no data about attributable to bedaquiline adverse events in MDR-TB/HIV co-infected pregnant women and their fetus as well as during the postpartum period.